2016
DOI: 10.5194/hess-20-3907-2016
|View full text |Cite
|
Sign up to set email alerts
|

Areal rainfall estimation using moving cars – computer experiments including hydrological modeling

Abstract: Abstract. The need for high temporal and spatial resolution precipitation data for hydrological analyses has been discussed in several studies. Although rain gauges provide valuable information, a very dense rain gauge network is costly. As a result, several new ideas have emerged to help estimating areal rainfall with higher temporal and spatial resolution. Rabiei et al. (2013) observed that moving cars, called RainCars (RCs), can potentially be a new source of data for measuring rain rate. The optical sensor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…UAV should be applied in the field of hydrological information acquisition because of their flexibility, simplicity, and speed, especially in relation to river discharges. Previous studies have shown that many rough observations may result in better data compared with few accurate experiments [68,69]. UAV, as a kind of low-cost equipment, can obtain information simply and quickly.…”
Section: Leading Role Of Uav Remote Sensing and Its Limitationsmentioning
confidence: 99%
“…UAV should be applied in the field of hydrological information acquisition because of their flexibility, simplicity, and speed, especially in relation to river discharges. Previous studies have shown that many rough observations may result in better data compared with few accurate experiments [68,69]. UAV, as a kind of low-cost equipment, can obtain information simply and quickly.…”
Section: Leading Role Of Uav Remote Sensing and Its Limitationsmentioning
confidence: 99%
“…Resorting to inexpensive commercial products has stimulated scientists' inventive capabilities, thus leading to unintended electronics being used as hydrological sensors. For instance, precipitation has been measured with moving cars (Rabiei et al 2016) and accelerometers (Stewart et al 2012), and water levels have been monitored with game-console remote controls (Hut et al 2010). These research activities have facilitated the acquisition of hydrological data and have also paved the way for the implementation of public and collaborative sensing platforms (for instance, Crowd Hydrology, OPEnS Lab and others).…”
Section: Introductionmentioning
confidence: 99%
“…A larger-scale example includes the Community Collaborative Rain, Hail, and Snow Network in the USA, (https://www.cocorahs.org/), which receive approximately 20 000 daily rain-gauge reports from citizen scientists across North America (Reges et al, 2016). In a particularly novel application of exploiting existing networks of data, Rabiei et al (2016) inferred rainfall by utilizing a vehicles GPS location together with sensors attached to the cars windscreen wipers. Many late-model vehicles employ infrared (or optical) sensors to determine rainfall intensity in order to automatically adjust the wiper rate, offering the possibility of providing distributed records of rainfall: albeit limited to the road network.…”
Section: Mobile Phones and Citizen Sciencementioning
confidence: 99%